2005
DOI: 10.1620/tjem.207.149
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Warm Fluid in Acute Burn Resuscitation: An Experimental Study in Dogs

Abstract: NAKAZAWA, H. and NOZAKI, M. Usefulness of Warm Fluid in Acute Burn Resuscitation: An Experimental Study in Dogs. Tohoku J. Exp. Med., 2005, 207 (2), [149][150][151][152][153][154][155] Hypothermia is a common complication in patients with extensive burns, receiving massive volumes of fluid for resuscitation at ambient temperature. It is therefore important to maintain the body temperature of patients with extensive burns. The present study was performed to evaluate the usefulness of warm fluid for burn injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The administration of unwarmed IV fluids or blood products is a cause of hypothermia that has been associated with adverse outcomes in human studies . Hypothermia secondary to fluid administration can be prevented by the warming of IV solutions . We chose the TEMPCARE as a readily available and affordable example of a veterinary specific in‐line fluid warmer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of unwarmed IV fluids or blood products is a cause of hypothermia that has been associated with adverse outcomes in human studies . Hypothermia secondary to fluid administration can be prevented by the warming of IV solutions . We chose the TEMPCARE as a readily available and affordable example of a veterinary specific in‐line fluid warmer.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have demonstrated that prewarmed fluid administration can be effective in minimizing hypothermia . This has been associated with improved postoperative hemodynamic performance, decreased incidence of shivering, and shorter recovery times …”
Section: Introductionmentioning
confidence: 99%
“…Hypothermia is a common complication in SBI patients. Cooling of burn wounds, large‐volume fluid resuscitation, low ambient temperatures, topical wound treatments, and prolonged surgical procedures all contribute to hypothermia . Hypothermia can have profound adverse effects on coagulation, drug metabolism, oxygen consumption, and risk of infection .…”
Section: Complicationsmentioning
confidence: 99%
“…Cooling of burn wounds, large‐volume fluid resuscitation, low ambient temperatures, topical wound treatments, and prolonged surgical procedures all contribute to hypothermia . Hypothermia can have profound adverse effects on coagulation, drug metabolism, oxygen consumption, and risk of infection . Attempts to maintain normal body temperature in burn patients include warming the room to 33°C (91.4°F) to decrease evaporative losses, warming inspired air, utilizing warming blankets and countercurrent heat exchangers for infused fluids .…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation